2001
DOI: 10.1002/path.926
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fas and Fas ligand in uveal melanoma: biological implication and prognostic value

Abstract: The interaction between Fas and Fas ligand is one possible immune escape mechanism used by tumour cells. In the present study, melanoma tissue from 103 patients who underwent enucleation for malignant uveal melanoma (iris melanomas excluded) was stained by immunohistochemistry with monoclonal antibodies specific for Fas, Fas ligand, CD3, CD8, and CD68. Histological and clinical data for these tumours were assessed. Both Fas and Fas ligand were detected in uveal melanomas. Cells of the monocyte/macrophage linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…It has been recently demonstrated that UMM cells produce soluble FasL that binds to the surface of neoplastic cells, protecting them from Fas-induced cell death (49). Anastiassiou et al (12) showed FasL expression in most of 103 clinically wellcharacterized cases of UMM. These authors, however, did not find a decreased number of TIL in FasL expressing tumors, as had been expected based on the data published on other FasL positive tumors inducing apoptosis of the Fas-positive leukocytes (50).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently demonstrated that UMM cells produce soluble FasL that binds to the surface of neoplastic cells, protecting them from Fas-induced cell death (49). Anastiassiou et al (12) showed FasL expression in most of 103 clinically wellcharacterized cases of UMM. These authors, however, did not find a decreased number of TIL in FasL expressing tumors, as had been expected based on the data published on other FasL positive tumors inducing apoptosis of the Fas-positive leukocytes (50).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that increased soluble Fas/CD95 serum levels correlate with poor prognosis in melanoma patients [17]. In uveal melanoma, metastasisfree 5-year survival rates were considerably lower in patients with tumors that lacked FasL/CD95L expression [18]. In the present study, immunohistochemistry was used to examine Fas/CD95 and FasL/CD95L expression in pathologically and clinically well-characterized cases of cutaneous malignant melanoma.…”
Section: Introductionmentioning
confidence: 90%
“…There are conflicting reports of the expression of FAS and FASligand (tumor suppressor proteins of the tumor necrosis family) in melanomas and nevi and neither has been shown to be an independent prognostic factor. [110][111][112] Flice inhibitory protein was studied by Bullani et al 113 and identified in 24 of 29 melanomas but only 1 of 32 benign nevi. Cancer/testis antigens are proteins normally expressed only in the testis but aberrantly expressed in many types of malignancies.…”
Section: Markers Of Tumor Cell Proliferationmentioning
confidence: 99%